In vitro and in vivo Metabolism of a Potent Inhibitor of Soluble Epoxide Hydrolase, 1-(1-Propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy)phenyl)urea - Wan, Debin; Yang, Jun; McReynolds, Cindy B.; Barnych, Bogdan; Wagner, Karen M.; Morisseau, Christophe; Hwang, Sung Hee; Sun, Jia; Blöcher, René; Hammock, Bruce D. (Frontiers in Pharmacology, 2019)
1-(1-Propionylpiperidin-4-yl)-3-(4-(trifluoromethoxy)phenyl)urea (TPPU) is a potent soluble epoxide hydrolase (sEH) inhibitor that is used extensively for modulating inflammation and protecting against hypertension, neuropathic pain and neurodegeneration. Despite its wide use in various animal disease models, the metabolism of TPPU has not been well studied. Herein, we describe the identification of TPPU metabolites using LC-MS/MS strategies. Four metabolites (M1-M4) were identified from rat urine by a sensitive LC-MS/MS method with double precursor ion scans. Their structures were further supported by LC-MS/MS comparison with synthesized standards. M1 and M2 were formed from hydroxylation on a propionyl group; M3 was formed by amide hydrolysis of the 1-propionylpiperdinyl group; and M4 was formed by further oxidation of M2. Interestingly, the predicted -diketone metabolite and 4-(trifluoromethoxy)aniline (formed from urea cleavage) were not detected by LC-MRM-MS method. This indicates that if formed, the two potential metabolites represent <0.01% of TPPU metabolism. Species differences in the formation of these 4 identified metabolites was assessed using liver S9 fractions from dog, monkey, rat, mouse, and human. M1, M2 and M3 were generated in liver S9 fractions from all species, and higher amounts of M3 were generated in monkey S9 fractions compared to other species. In addition, rat and human S9 metabolism showed the highest species similarity based on the quantities of each metabolite. Aniline, M4 or other unidentified metabolites were not observed in any of the liver S9 incubations. The presence of all 4 metabolites were confirmed in vivo in rats over 72-hours post single oral dose of TPPU. M1, M2, M3 and M4 were detected both in urine and blood: M1 accounted for approximately 9.6% of the total TPPU-related exposure in blood, while metabolites M2, M3 and M4 accounted for less than 0.4%. All 4 metabolites were potent inhibitors of human sEH but were less potent than the parent TPPU. In conclusion, TPPU is metabolized via oxidation and amide hydrolysis without apparent breakdown of the urea. Our findings increase the confidence in the ability to translate preclinical PK of TPPU in rats to humans and facilitates the potential clinical development of TPPU and other sEH inhibitors.